Unmasking P.T. Barnum: A Character Study of the Greatest Showman - Barlian; I Wayan Juniartha (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study analyzes the character development of P.T. Barnum in The Greatest Showman (2017) using Egri’s (1960) three-dimensional character theory, physiological, sociological, and psychological, and is supported by Kenny’s (1966) narrative coherence framework. Employing a descriptive qualitative method, the study examines nine selected scenes that represent the beginning, middle, and end of the film. The analysis is conducted in a multimodal manner, integrating verbal elements (dialogue, narration) and visual cues (gestures, posture, costumes, facial expressions). Findings indicate that Barnum’s character transformation is balanced across three aspects: physiological (33.3%), sociological (33.3%), and psychological (33.4%). His physical appearance evolves from a playful child to a confident showman and finally to a humble family man. Sociologically, his pursuit of social status leads to internal conflict and distancing from his original community. Psychologically, Barnum's ambition and insecurity drive his decisions until he eventually finds emotional resolution. The study demonstrates how Egri’s and Kenny’s theories can be integrated to provide a comprehensive understanding of character construction in film. These findings offer theoretical contributions to character and narrative analysis, and practical insights for film studies, media education, and applied linguistics.